Implementation of Classical Guidance Services Using Game Based Learning Techniques to Prevent Juvenile Delinquency in SMK Negeri 4 Medan - Daulay, Khoirunnisa; Deliati, Deliati; Magdalena, Magdalena (Lembaga Riset Mutiara Akbar, 2025)
This study aims to prevent juvenile delinquency in students of SMK Negeri 4 Medan by implementing classical guidance services using game-based learning techniques. The research method used is classroom action research with subjects of 22 students of class XI TAV 1 who have a moderate level of juvenile delinquency based on pre-cycle results. Services are provided in two cycles with digital mystery box media and interactive game-based learning activities. The pre-cycle results show that 100% of students are in the moderate category with an average score of 117.82. After cycle I, there was a decrease in delinquency with an average score of 94.73 and 27.27% of students were in the low category, but the success target had not been achieved. In cycle II, there was a significant increase where 77.27% of students were in the low category with an average score of 81.05, exceeding the target of greater than or equal to 76%. These findings indicate that the application of game-based learning in classical guidance services is effective in increasing students' awareness of the consequences of delinquency and encouraging more positive behavior. This study underlines the importance of engaging and collaborative learning approaches in efforts to prevent juvenile delinquency in schools.